Earthworm species in various land use systems in the Campos Gerais region of Lapa, Paraná, Brazil - Demetrio, Wilian C.; Santos, Alessandra; Ferreira, Talita; Nadolny, Herlon; Cardoso, Guilherme B.x.; Torres, Julia L.m.; Dudas, Rafaela; de Oliveira, Viviane; Barreto, Julia O.; James, Samuel W.; Da Silva, Elodie; Brown, George G.; et al. (Zootaxa, 2018)
The Campos Gerais region of Paraná are on an ancient plateau of sandstone origin and are covered with a diverse vegetation including mainly grasslands and various types of Atlantic Forest (particularly Araucaria forest). The region represents an important natural capital for biodiversity conservation as well as for agricultural and forestry production. However, little is known of the species richness and diversity of soil macroinvertebrates in this region. In the present study we evaluated earthworm species occurrence and richness in five land use systems (LUS) in the southern part of the Campos Gerais in Lapa county. Earthworms were handsorted from up to 18 soil monoliths on five occasions over three years (Feb. 2014, Feb., Mar., Nov. 2015, Jul. 2016) in the following LUS: old native forest, native grassland, young regenerating forest and grass lawn in the Uru Reserve and annual crop fields (soybean) in neighboring private farms (not all systems were sampled on all occasions). Nine earthworm species belonging to four families and five genera were found, of which six were native and three exotic species (Dichogaster gracilis, Amynthas gracilis, A. corticis). Of the native species, Urobenus brasiliensis and Andiorrhinus duseni (a large bodied-worm) are already well known from S and SE Brazil, while the remaining four were new species that require further description (Fimoscolex n.sp.1 and n.sp.2, Glossoscolex n.sp.1 and n.sp.2). In general, more species were found in February (summer) than March and November. The cropping system (soybean) had the lowest abundance and species richness in relation to other sites, although in the young and old forests no earthworms were found on some sample dates. Given the several new species found in this small reserve, and the relatively few sites studied thus far in the Campos Gerais, further efforts are needed to adequately characterize the earthworm fauna of the region, from which many other species are expected.